2015
DOI: 10.6017/eurj.v11i2.9062
|View full text |Cite
|
Sign up to set email alerts
|

Latino Masculinity: Underlying Factors in College Persistence Levels

Abstract: Despite growing numbers, Latinos lag behind whites in higher education. This gap is especially salient for Latino men, who earned only 37.6 percent of associate's and bachelor's degrees awarded to Latino students in 2010. The following study uses interviews with thirteen ethnically diverse, first-generation, self-identified Latino men currently enrolled in four-year universities in the Greater Boston area to explore the influences Latino men idetnify as impacting their collge success and persistence rates. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As a part of the study, participants shared a re-occurring experience where their friends, who identified as Latino men, made it a point to clearly identify any male individual who expressed feelings that could be deemed too sensitive. The participants of this study qualified these experiences by suggesting that their Latino friends were much more concerned with “acting stereotypically male” (Vasquez, 2015, p. 37). The gender policing that Latino men practice and reinforce greatly limits their capacity to perform alternate forms of masculinity (Saez et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 58%
See 2 more Smart Citations
“…As a part of the study, participants shared a re-occurring experience where their friends, who identified as Latino men, made it a point to clearly identify any male individual who expressed feelings that could be deemed too sensitive. The participants of this study qualified these experiences by suggesting that their Latino friends were much more concerned with “acting stereotypically male” (Vasquez, 2015, p. 37). The gender policing that Latino men practice and reinforce greatly limits their capacity to perform alternate forms of masculinity (Saez et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 58%
“…These narratives are reinforced by the messaging the participants received via interactions with peers who identified as men (Circle No. 2) through gender policing (Mora, 2013; Vasquez, 2015). The participants clearly stated what would happen to anyone who did not perform appropriately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The women in the lives of the participants all played influential roles that are critical toward transfer success for Latino men. Acting as out-of-class validating agents, participants' girlfriends provided navigational awareness of educational spaces; bonds with grandmothers, mothers, sisters, and aunts played a significant role in advising, motivation and supporting these men in their transfer process (Vazquez, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a qualitative study on Latinos young men found that hyper-policing often occurs among them. There is an expectation of emotional stoicism, "manliness," and machismo, against emotional difficulties or vulnerabilities (Vazquez, 2015) that may be critical to the Latino man. This may explain their tendency to cope solitarily in ways that may reflect characteristics that may be seen more with depression than anxiety.…”
Section: Discussionmentioning
confidence: 99%